Unraveling the complexities of the HDL lipidome1 - Anatol Kontush; Marie Lhomme; M. John Chapman (Journal of Lipid Research, 2013)
Plasma high density lipoproteins (HDL) are small, dense, protein-rich particles compared with other lipoprotein classes; roughly half of total HDL mass is accounted for by lipid components. Phospholipids predominate in the HDL lipidome, accounting for 40–60% of total lipid, with lesser proportions of cholesteryl esters (30–40%), triglycerides (5–12%), and free cholesterol (5–10%). Lipidomic approaches have provided initial insights into the HDL lipidome with identification of over 200 individual molecular lipids species in normolipidemic HDL. Plasma HDL particles, however, reveal high levels of structural, compositional, and functional heterogeneity. Establishing direct relationships between HDL structure, composition, and atheroprotective functions bears the potential to identify clinically relevant HDL subpopulations. Furthermore, development of HDL-based therapies designed to target beneficial subspecies within the circulating HDL pool can be facilitated using this approach. HDL lipidomics can equally contribute to the identification of biomarkers of both normal and deficient HDL functionality, which may prove useful as biomarkers of cardiovascular risk. However, numerous technical issues remain to be addressed in order to make such developments possible. With all technical questions resolved, quantitative analysis of the molecular components of the HDL lipidome will contribute to expand our knowledge of cardiovascular and metabolic diseases.